Review of space charge measurement by pulsed electro-acoustic technique - Mohd Haris Asyraf Shee Kandar; Nor Akmal Mohd Jamail; Nordiana Azlin Othman; Qamarul Ezani Kamarudin; Nor Shahida Mohd Jamail; Susama Bagchi (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
Pulsed electro-acoustic (PEA) is well known as a non-destructive technique for testing and describing space charge profiles in the insulation. Degradation due to moisture, ageing, external flashover, partial discharge and space charge are considered as insulation defects that is an issue in high voltage insulator. Space charge may distort the internal electric field that may lead to an electrical breakdown. For instance, a method based on an acoustic phenomenon can be used to describe the space charge profiles. This paper compares several earlier researches on different specimen of PEA method and reviews their results to find the space charge distribution profiles. The scope of the review includes types of methods used. The acoustic technique is considered for this study. It has been observed that the PEA technique successfully gives the same result as theoretical that is based on the obtained profile. Linear low-density polyethylene (LLDPE) composite demonstrates about 89 % lower charge density value compared to cross-linked polyethylene (XLPE) and polypropylene (PP) composite. While the electric field value of ethylene-vinyl acetate (EVA) sample is 75 % lower than low-density polyethylene (LDPE) sample. This study found that the time interval, specimen thickness and the electric field sway the space charge profiles.